Diversified recycling strategies for high-end plastics: Technical feasibility and impact assessment. Issue 1 (2019) - Dewulf, Wim; Wagner, Florian; Bracquené, Ellen; Peeters, Jef R.; Duflou, Joost R.
Abstract: Waste Electrical and Electronic Equipment (WEEE) comprises a complex mix of engineering plastic grades often containing flame retardants. Whereas post-shredder recycling strategies are widely implemented, considerably higher economic and environmental returns can be expected based on information-rich dismantling scenarios. This paper therefore presents the results of an extensive technological feasibility study on diversified recycling strategies for a dismantling based approach. Results of mechanical and flammability tests as well as injection moulding trials are moreover presented to show the quality and potential of the recycling strategies. Subsequently, the environmental impact reduction potential is assessed using Life Cycle Assessment.